Rationing proposed training program to reduce of blood pressure to the elderly - Experimental study For the elderly with blood pressure in Khamis Maliana - bouali lakhdar; bachir nemroud; nassar mohamed (sports creativity, 2025)
The importance of the study is the exercise of older people for sports activities on the basis of scientific and organized, which led us to prepare a training program to know its effect on the alleviation of high blood pressure in the elderly (40-70 years). The experimental method was adopted by measuring and measuring The study sample consisted of a voluntary sample consisting of 18 members of the study population, namely, the elderly group with hypertension in the city of Khamis Maliana, 9 of whom were experimental samples (the program was applied) and 9 others as control samples. A training program consisting of 16 training modules for 8 weeks, after being presented to specialists In order to match the characteristics of the research sample, after the tribal measurement and telemetry.The results resulted in a series of results, the most important of which are: The training program has a positive effect on the elderly, as it contributed to the improvement of physiological variables There are statistically significant differences between the tribal measurement and the post-measurement measurement of blood pressure in the experimental group